2022
DOI: 10.1002/hyp.14538
|View full text |Cite
|
Sign up to set email alerts
|

Higher canopy interception capacity of forests restored to the climax stage in subtropical China

Abstract: Canopy interception loss is an important hydrological process that affects rainfall redistribution, nutrient cycling, and soil and water conservation in forest ecosystems. However, the manner in which interception loss is affected in forests that are in restoration stages dominated by different tree species has not been fully understood. In this study, interception loss, throughfall, and stemflow were measured consecutively for 2 years (May 2017 through April 2019) in three secondary forests in subtropical Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Tao et al (2021) showed that transpiration increases because tree roots tend to go deeper with age, thus extracting soil water from layers that have not been often quantified due to methodological constraints. If the leaf area index tends to increase across the tropical forest succession (Kal acska et al 2004), so is expected to increase rain interception by the canopies, as demonstrated by Sun et al (2022).…”
Section: Increasing Tree Canopy Cover and Biomass Reduces The Effecti...mentioning
confidence: 99%
“…Tao et al (2021) showed that transpiration increases because tree roots tend to go deeper with age, thus extracting soil water from layers that have not been often quantified due to methodological constraints. If the leaf area index tends to increase across the tropical forest succession (Kal acska et al 2004), so is expected to increase rain interception by the canopies, as demonstrated by Sun et al (2022).…”
Section: Increasing Tree Canopy Cover and Biomass Reduces The Effecti...mentioning
confidence: 99%
“…Vegetation canopy interception is the process by which gross rainfall falling onto plant surfaces is captured, stored, and subsequently lost through evaporation from the canopy [1]. This process represents water loss from ecosystems and water gain for the atmosphere, and as such it plays a critical role in regulating the global hydrological cycle and land-atmosphere interactions [2,3]. It has been widely reported that canopy interception accounts for more than 20% of the gross rainfall across biomes globally [4], even exceeding 40% in some forest-covered regions [5,6].…”
Section: Introductionmentioning
confidence: 99%